Resin composition for sealing
A tailored polyester resin blend with specific properties addresses adhesion and oil resistance issues, providing robust sealing for electrical and electronic components.
Patent Information
- Application Number
- JP2020206017
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-11
- Filing Date
- 2020-12-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-12-11
AI Technical Summary
Existing sealing resins for electrical and electronic components face challenges in achieving sufficient adhesion, melt viscosity, and oil resistance, particularly when exposed to oils, leading to compromised sealing performance.
A sealing resin composition comprising a specific blend of polyester resins with varying polyalkylene glycol content and specific gravity ratios, along with an antioxidant, to enhance adhesiveness, melt viscosity, and oil resistance.
The resin composition provides excellent adhesiveness, melt viscosity, and oil resistance, ensuring durable and effective sealing of electrical and electronic components.
Smart Images

Figure 0007600660000004 
Figure 0007600660000001 
Figure 0007600660000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an encapsulating resin composition, and more particularly to an encapsulating resin composition capable of encapsulating electric and electronic components. [Background technology]
[0002] Two-component curing epoxy resins and silicone resins have generally been used as insulating resins for sealing electrical and electronic components used in automobiles, electrical appliances, and the like. However, because of the long process time required and the possibility of damaging the electrical and electronic components due to shrinkage stress during curing, in recent years, sealing of electrical and electronic components by low-pressure molding with thermoplastic resins has been proposed (e.g., Patent Document 1).
[0003] When sealing electrical and electronic components using the above-mentioned low-pressure molding, excellent adhesion to glass-epoxy substrates (glass-epoxy: layers of glass fiber cloth impregnated with epoxy resin) and polyester substrates such as PET and PBT is required from the standpoint of waterproofing.
[0004] In addition to the above adhesiveness, polyester resins are used as a suitable material as sealing resins for electrical and electronic components from the viewpoints of electrical insulation, water resistance, durability, and melt viscosity, but in low-temperature, low-pressure molding to reduce damage to electrical and electronic components, the adhesiveness between the electrical and electronic components and the sealing resin is insufficient, and the intended electrical insulation and waterproofing properties are often not fully exhibited. Therefore, attempts to incorporate adhesion promoters having functional groups, etc., from the viewpoint of improving the adhesiveness are being actively studied (for example, Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2012-117044 A [Patent Document 2] JP 2004-210893 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0006] On the other hand, in addition to the required physical properties as described above, oil resistance is sometimes required for electric and electronic components. However, when a thermoplastic resin as disclosed in Patent Document 1 or a thermoplastic resin containing an adhesion promoter as disclosed in Patent Document 2 is used, there is a problem that the thermoplastic resin absorbs oily components in an oil resistance test and swells, so that the sealing performance is not ensured.
[0007] As described above, no conventional techniques have proposed a resin composition that satisfies the required performance in terms of oil resistance as an encapsulating resin composition.
[0008] The present invention has been made in view of the problems of the conventional art. That is, an object of the present invention is to provide an excellent encapsulating resin composition that ensures adhesion and melt viscosity without causing deterioration in oil resistance, particularly physical properties when immersed in kerosene. In particular, the encapsulating resin composition of the present invention is suitable for encapsulating electric and electronic components. [Means for solving the problem]
[0009] As a result of extensive investigations, the present inventors have found that the above problems can be solved by the means shown below, and have arrived at the present invention. That is, the present invention has the following configuration.
[0010] A resin composition for sealing electric and electronic components, comprising: a polyester resin (A) having a specific gravity of less than 1.20 and containing polyalkylene glycol as a copolymerization component; and a polyester resin (B) having a specific gravity of 1.20 or more and containing no polyalkylene glycol as a copolymerization component, wherein the mass ratio M(A):M(B) of the polyester resin (A) to the polyester resin (B) is 90:10 to 70:30.
[0011] The resin composition for sealing electric and electronic components preferably further contains an antioxidant (C). Effect of the Invention
[0012] The resin composition for sealing electric and electronic components of the present invention has excellent adhesion, melt viscosity and oil resistance. Therefore, by using the resin composition as a sealant in a sealed electric and electronic component, it is possible to produce a sealed electric and electronic component having excellent adhesion and oil resistance. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 shows a schematic diagram of a chart measured by a differential scanning calorimeter. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below.
[0015] <Polyester resin (A)> The polyester resin (A) used in the present invention is a resin containing polyalkylene glycol as a copolymerization component. The polyester resin (A) preferably has a chemical structure in which a hard segment mainly composed of a polyester segment and a soft segment mainly composed of a polyalkylene glycol component are bonded by an ester bond. The polyester segment is preferably mainly composed of a polyester having a structure that can be formed by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol and / or an alicyclic glycol. The hard segment is preferably contained in an amount of 20 mol% to 80 mol% in the entire polyester resin (A), more preferably 30 mol% to 70 mol% in the entire polyester resin (A), and even more preferably 40 mol% to 60 mol% in the entire polyester resin (A). The soft segment is preferably contained in an amount of 20 mol% to 80 mol% in the entire polyester resin (A), more preferably 30 mol% to 70 mol% in the entire polyester resin (A), and even more preferably 40 mol% to 60 mol% in the entire polyester resin (A). By setting the hard segment and the soft segment within the above range, the adhesion of the encapsulating resin composition is improved.
[0016] The specific gravity of the polyester resin (A) used in the present invention must be less than 1.20. In order to improve the adhesiveness, it is preferably 1.18 or less, and more preferably 1.15 or less. The lower limit is not particularly limited, but it is sufficient as long as it is 0.90 or more, and it may be 1.00 or more.
[0017] The upper limit of the ester group concentration of the polyester resin (A) used in the present invention is 8000 equivalents / 10 6 g. A more preferred upper limit is 7500 equivalents / 10 6 g, and more preferably 7000 equivalents / 10 6 g. Also, when chemical resistance (gasoline, engine oil, alcohol, general-purpose solvents, etc.) is required, the lower limit is 1000 equivalents / 10 6 g. A more preferable lower limit is 1500 equivalents / 10 6 g, and more preferably 2000 equivalents / 10 6 g. Here, the unit of the ester group concentration is 10 6 It is expressed as the number of equivalents per gram and can be calculated from the composition of the polyester resin (A) and its copolymerization ratio.
[0018] The acid value of the polyester resin (A) used in the present invention is 50 equivalents / 10 6 g or less, and more preferably 30 equivalents / 10 6 g or less, and more preferably 20 equivalents / 10 6 g or less. By making the acid value equal to or less than the upper limit, hydrolysis of the polyester resin (A) caused by the acid generated from the carboxylic acid can be suppressed, and a decrease in the resin strength can be suppressed. The lower limit of the acid value is not particularly limited, but is preferably 1 equivalent / 10 6 g or more, and more preferably 5 equivalents / 10 6 By making the acid value equal to or more than the lower limit, the adhesiveness becomes good.
[0019] The lower limit of the number average molecular weight of the polyester resin (A) used in the present invention is not particularly limited, but is preferably 3,000 or more, more preferably 5,000 or more, and even more preferably 7,000 or more. The upper limit of the number average molecular weight is not particularly limited, but is preferably 60,000 or less, more preferably 50,000 or less, and even more preferably 40,000 or less. By making the number average molecular weight equal to or more than the lower limit, the hydrolysis resistance of the resin composition for sealing electric and electronic components (hereinafter, also simply referred to as the sealing resin composition) and the retention of strength and elongation under high temperature and high humidity are improved. On the other hand, by making it equal to or less than the upper limit, the melt viscosity of the sealing resin composition does not become too high, and therefore the molding pressure can be kept low.
[0020] The polyester resin (A) used in the present invention is preferably a saturated polyester resin, and has an equivalent weight of 50 / 10 6 It is also preferable that the unsaturated polyester resin has a minute amount of vinyl groups of 1 g or less. By making the vinyl group concentration equal to or less than the above value, crosslinking during melting is suppressed, and melt stability is improved.
[0021] The polyester resin (A) used in the present invention may be a branched polyester obtained by copolymerizing a tri- or higher functional polycarboxylic acid or polyol such as trimellitic anhydride or trimethylolpropane, if necessary.
[0022] In order to mold the polyester resin (A) used in the present invention without causing thermal degradation as much as possible, rapid melting at 210 to 240°C is required. For this reason, the upper limit of the melting point of the polyester resin (A) is preferably 210°C. More preferably, it is 200°C, and even more preferably, it is 190°C. Considering the ease of handling at room temperature and normal heat resistance, it is preferably 70°C or higher, more preferably 100°C or higher, even more preferably 120°C or higher, particularly preferably 140°C or higher, and most preferably 150°C or higher. It is preferably 5 to 10°C higher than the heat resistance temperature required for the corresponding application.
[0023] The glass transition temperature of the polyester resin (A) is preferably less than −20° C., more preferably not more than −30° C., and even more preferably not more than −40° C. Also, it is preferably not less than −100° C., more preferably not less than −90° C., and even more preferably not less than −80° C. By keeping it within the above range, the adhesive strength of the encapsulating resin composition becomes good.
[0024] The melt viscosity of the polyester resin (A) at 200°C is preferably 3000 dPa·s or less. Since the melt viscosity of the encapsulating resin composition decreases, it is more preferably 2500 dPa·s or less, and further preferably 2000 dPa·s or less. There is no particular lower limit, but from an industrial perspective, it is sufficient that it is 100 dPa·s or more, and it may be 200 dPa·s or more. The melt viscosity of the polyester resin (A) is preferably lower than that of the polyester resin (B).
[0025] The polyester resin (A) used in the present invention can be produced by a known method. For example, a polyester can be obtained by esterifying a polycarboxylic acid component and a polyol component described below at 150 to 250°C, followed by polycondensation at 230 to 300°C while reducing pressure. Alternatively, a polyester can be obtained by using a derivative of a polycarboxylic acid such as a dimethyl ester described below and a polyol component to perform an ester exchange reaction at 150 to 250°C, followed by polycondensation at 230 to 300°C while reducing pressure.
[0026] <Hard segment of polyester resin (A)> The hard segment of the polyester resin (A) of the present invention preferably consists mainly of a polyester segment.
[0027] The acid component constituting the polyester segment is not particularly limited, but it is preferable that it contains an aromatic dicarboxylic acid having 8 to 14 carbon atoms, since it can improve the heat resistance of the polyester resin (A). In addition, it is preferable that the aromatic dicarboxylic acid having 8 to 14 carbon atoms is terephthalic acid and / or naphthalenedicarboxylic acid, which is highly reactive with glycol, and is preferable in terms of polymerizability and productivity. In addition, when the total acid components of the polyester resin (A) are taken as 100 mol%, the total of terephthalic acid and naphthalenedicarboxylic acid is preferably 50 mol% or more, more preferably 60 mol% or more, even more preferably 80 mol% or more, and particularly preferably 95 mol% or more, and it is acceptable that the total acid components are composed of terephthalic acid and / or naphthalenedicarboxylic acid.
[0028] Examples of other acid components constituting the polyester segment include aromatic dicarboxylic acids such as diphenyldicarboxylic acid, isophthalic acid, orthophthalic acid, and 5-sodium sulfurisophthalic acid, alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid and tetrahydrophthalic anhydride, and aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, dodecanedioic acid, dimer acid, and hydrogenated dimer acid. These dicarboxylic acid components are used in a range that does not significantly lower the melting point of the polyester resin (A), and the copolymerization ratio is preferably 50 mol% or less, more preferably 40 mol% or less, even more preferably 20 mol% or less, and particularly preferably 5 mol% or less, and may be 0 mol%, when the total acid components of the polyester resin (A) are taken as 100 mol%. These acid components can be used alone or in combination of two or more. In addition, it is also possible to use trifunctional or higher polycarboxylic acids such as trimellitic acid and pyromellitic acid as other acid components constituting the polyester segment. From the viewpoint of preventing gelation of the encapsulating resin composition, the copolymerization ratio of the tri- or higher functional polycarboxylic acid is preferably 10 mol % or less, and more preferably 5 mol % or less, of the total acid components of the polyester resin (A).
[0029] The aliphatic glycol and / or alicyclic glycol constituting the polyester segment is not particularly limited, but is preferably an alkylene glycol having 2 to 10 carbon atoms, and more preferably an alkylene glycol having 2 to 8 carbon atoms. The aliphatic glycol and / or alicyclic glycol is preferably contained in an amount of 50 mol% or more, more preferably 60 mol% or more, even more preferably 65 mol% or more, and particularly preferably 70 mol% or more, when the total glycol component is taken as 100 mol%. Also, it is preferably contained in an amount of 90 mol% or less, more preferably 85 mol% or less, even more preferably 80 mol% or less, and particularly preferably 75 mol% or less. Specific examples of preferred glycol components include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,4-cyclohexanedimethanol. 1,4-butanediol and 1,4-cyclohexanedimethanol are more preferred in that they can improve the heat resistance of the polyester resin (A), and 1,4-butanediol is most preferred. In addition, as part of the glycol component, a trifunctional or higher polyol such as glycerin, trimethylolpropane, or pentaerythritol may be used. From the viewpoint of preventing gelation of the encapsulating resin composition, the amount of the trifunctional or higher polyol is preferably 10 mol % or less, and more preferably 5 mol % or less, of the total glycol components of the polyester resin (A).
[0030] As the component constituting the polyester segment, those consisting of butylene terephthalate units or butylene naphthalate units are particularly preferred in terms of the polyester resin (A) having a high melting point and thus improving heat resistance, as well as moldability and cost performance.
[0031] <Soft segment of polyester resin (A)> The soft segment of the polyester resin (A) of the present invention is preferably mainly composed of a polyalkylene glycol component. The copolymerization ratio of the soft segment is preferably 10 mol% or more, more preferably 15 mol% or more, even more preferably 20 mol% or more, and particularly preferably 25 mol% or more, when the total glycol components constituting the polyester resin (A) are taken as 100 mol%. Also, it is preferably 50 mol% or less, more preferably 40 mol% or less, even more preferably 35 mol% or less, and particularly preferably 30 mol% or less. By setting the copolymerization ratio of the soft segment to the lower limit or more, the melt viscosity of the encapsulating resin composition can be kept low, and molding can be performed at a low pressure. Furthermore, the crystallization rate can be suppressed, and the occurrence of short shots can be suppressed. Also, by setting the copolymerization ratio of the soft segment to the upper limit or less, the heat resistance of the encapsulating resin composition can be improved.
[0032] The number average molecular weight of the soft segment is not particularly limited, but is preferably 400 or more, more preferably 800 or more. By making the number average molecular weight of the soft segment equal to or more than the lower limit, flexibility can be imparted to the encapsulating resin composition, and the stress load on the electronic substrate after encapsulation can be reduced. In addition, the number average molecular weight of the soft segment is preferably 5000 or less, more preferably 3000 or less. By making the number average molecular weight of the soft segment equal to or less than the upper limit, compatibility with other copolymerization components is improved, making copolymerization easier.
[0033] Specific examples of the polyalkylene glycol component used in the soft segment include polyethylene glycol, polytrimethylene glycol, polytetramethylene glycol, etc. From the viewpoints of imparting flexibility and reducing melt viscosity, polytetramethylene glycol is most preferred.
[0034] The polyester resin (A) of the present invention may be either amorphous or crystalline, but is more preferably a crystalline polyester resin. Being crystalline improves oil resistance. In the present invention, the crystalline polyester resin is measured by cooling the resin to -100°C using a differential scanning calorimeter (DSC) once and then heating the resin to 300°C at a speed of 20°C / min. The resin is then cooled from 300°C to -100°C at a speed of 50°C / min, and then heated again to 300°C at a speed of 20°C / min. The polyester resin shows a clear melting peak in either of these two heating steps. On the other hand, the amorphous polyester resin shows no melting peak in either heating step.
[0035] <Polyester resin (B)> The polyester resin (B) used in the present invention is a resin that does not contain polyalkylene glycol in the copolymerization component. The polyester resin (B) preferably has a chemical structure in which hard segments mainly composed of polyester segments are bonded, and more preferably has only a chemical structure in which the hard segments are bonded. The polyester segments are preferably mainly composed of polyesters having a structure that can be formed by polycondensation of aromatic dicarboxylic acids with aliphatic glycols and / or alicyclic glycols. The copolymerization component not containing polyalkylene glycol means that, when the glycol component constituting the polyester resin (B) is taken as 100 mol %, the content of polyalkylene glycol is preferably 1 mol % or less, more preferably 0.5 mol % or less, even more preferably 0.1 mol % or less, and particularly preferably 0 mol %.
[0036] The specific gravity of the polyester resin (B) used in the present invention must be 1.20 or more. In order to improve oil resistance, it is preferably 1.22 or more, and more preferably 1.25 or more. There is no particular upper limit, but it is sufficient if it is 1.50 or less, and it may be 1.40 or less.
[0037] The upper limit of the ester group concentration of the polyester resin (B) used in the present invention is 8000 equivalents / 10 6 g. A more preferred upper limit is 7500 equivalents / 106 g, and more preferably 7000 equivalents / 10 6 g. Also, when chemical resistance (gasoline, engine oil, alcohol, general-purpose solvents, etc.) is required, the lower limit is 1000 equivalents / 10 6 g. A more preferable lower limit is 1500 equivalents / 10 6 g, and more preferably 2000 equivalents / 10 6 g. Here, the unit of the ester group concentration is 10 6 It is expressed as the number of equivalents per gram and can be calculated from the composition of the polyester resin (B) and its copolymerization ratio.
[0038] The acid value of the polyester resin (B) used in the present invention is 60 equivalents / 10 6 g or less, and more preferably 50 equivalents / 10 6 g or less, and more preferably 40 equivalents / 10 6 g or less. By making the acid value equal to or less than the upper limit, hydrolysis of the polyester resin (B) caused by the acid generated from the carboxylic acid can be suppressed, and a decrease in the resin strength can be suppressed. The lower limit of the acid value is not particularly limited, but is preferably 10 equivalents / 10 6 g or more, and more preferably 20 equivalents / 10 6 By making the acid value equal to or more than the lower limit, the hydrolysis resistance becomes good.
[0039] The lower limit of the number average molecular weight of the polyester resin (B) used in the present invention is not particularly limited, but is preferably 3,000 or more, more preferably 5,000 or more, and even more preferably 7,000 or more. The upper limit of the number average molecular weight is not particularly limited, but is preferably 60,000 or less, more preferably 50,000 or less, and even more preferably 40,000 or less. By making the number average molecular weight equal to or more than the lower limit, the hydrolysis resistance of the encapsulating resin composition and the retention of strength and elongation under high temperature and high humidity conditions are improved. On the other hand, by making it equal to or less than the upper limit, the melt viscosity of the encapsulating resin composition does not become too high, and therefore the molding pressure can be kept low.
[0040] The polyester resin (B) used in the present invention is preferably a saturated polyester resin, and has an equivalent weight of 50 / 10 6 It is also preferable that the unsaturated polyester resin has a minute amount of vinyl groups of 1 g or less. By making the vinyl group concentration equal to or less than the above value, crosslinking during melting is suppressed, and melt stability is improved.
[0041] The polyester resin (B) used in the present invention may be a branched polyester obtained by copolymerizing a tri- or higher functional polycarboxylic acid or polyol such as trimellitic anhydride or trimethylolpropane, if necessary.
[0042] In order to mold the polyester resin (B) used in the present invention without causing thermal degradation as much as possible, rapid melting at 210 to 240°C is required. For this reason, the upper limit of the melting point of the polyester resin (B) is preferably 210°C. More preferably, it is 200°C, and even more preferably, it is 190°C. Considering the ease of handling at room temperature and normal heat resistance, it is preferably 70°C or higher, more preferably 100°C or higher, even more preferably 120°C or higher, particularly preferably 140°C or higher, and most preferably 150°C or higher. It is preferably 5 to 10°C higher than the heat resistance temperature required for the corresponding application.
[0043] The glass transition temperature of the polyester resin (B) is preferably -20°C or higher, more preferably -15°C or higher, and even more preferably -10°C or higher. Also, it is preferably 80°C or lower, more preferably 50°C or lower, and even more preferably 30°C or lower. By setting it within the above range, the oil resistance of the encapsulating resin composition becomes good. The glass transition temperature of the polyester resin (B) is preferably higher than the glass transition temperature of the polyester resin (A).
[0044] The melt viscosity of the polyester resin (B) at 200°C is preferably 3000 dPa·s or less. Since the melt viscosity of the encapsulating resin composition decreases, the melt viscosity is more preferably 2500 dPa·s or less, and further preferably 2000 dPa·s or less. The lower limit is not particularly limited, but industrially, it is sufficient that the melt viscosity is 100 dPa·s or more, and it may be 200 dPa·s or more.
[0045] The polyester resin (B) may be either amorphous or crystalline, but is preferably a crystalline polyester resin, since the resin has improved oil resistance.
[0046] The polyester resin (B) used in the present invention can be produced by a known method. For example, a polyester can be obtained by esterifying a polycarboxylic acid component and a polyol component described below at 150 to 250°C, followed by polycondensation at 230 to 300°C while reducing pressure. Alternatively, a polyester can be obtained by using a derivative of a polycarboxylic acid such as a dimethyl ester described below and a polyol component to perform an ester exchange reaction at 150 to 250°C, followed by polycondensation at 230 to 300°C while reducing pressure.
[0047] <Hard segment of polyester resin (B)> The hard segment of the polyester resin (B) of the present invention is preferably mainly composed of a polyester segment. The polyester segment in the polyester resin (B) is preferably 99% by mass or more, more preferably 99.5% by mass or more, further preferably 99.9% by mass or more, and particularly preferably 100% by mass.
[0048] The acid component constituting the polyester segment is not particularly limited, but preferably contains an aromatic dicarboxylic acid having 8 to 14 carbon atoms, which can improve the heat resistance of the polyester resin (B). The aromatic dicarboxylic acid having 8 to 14 carbon atoms is preferably terephthalic acid and / or naphthalenedicarboxylic acid, which has high reactivity with glycol, and is preferable in terms of polymerizability and productivity, and is more preferably terephthalic acid. When the total acid components of the polyester resin (B) are taken as 100 mol%, the content of terephthalic acid is preferably 50 mol% or more, more preferably 60 mol% or more, and even more preferably 70 mol% or more.
[0049] Examples of other acid components constituting the polyester segment include aromatic dicarboxylic acids such as diphenyldicarboxylic acid, isophthalic acid, orthophthalic acid, and 5-sodium sulfurisophthalic acid, alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid and tetrahydrophthalic anhydride, and aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, dodecanedioic acid, dimer acid, and hydrogenated dimer acid. These dicarboxylic acid components are used in a range that does not significantly lower the melting point of the polyester resin (B), and the copolymerization ratio is preferably 50 mol% or less, more preferably 40 mol% or less, and even more preferably 30 mol% or less, when the total acid components of the polyester resin (B) are taken as 100 mol%. These acid components can be used alone or in combination of two or more. In addition, it is also possible to use trifunctional or higher polycarboxylic acids such as trimellitic acid and pyromellitic acid as other acid components constituting the polyester segment. From the viewpoint of preventing gelation of the encapsulating resin composition, the copolymerization ratio of the tri- or higher functional polycarboxylic acid is preferably 10 mol % or less, and more preferably 5 mol % or less, of the total acid components of the polyester resin (B).
[0050] The aliphatic glycol and / or alicyclic glycol constituting the polyester segment is not particularly limited, but is preferably an alkylene glycol having 2 to 10 carbon atoms, and more preferably an alkylene glycol having 2 to 8 carbon atoms. The aliphatic glycol and / or alicyclic glycol is preferably contained in an amount of 80 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, particularly preferably 99 mol% or more, and may be 100 mol% when the total glycol components of the polyester resin (B) are taken as 100 mol%. Specific examples of preferred glycol components include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,4-cyclohexanedimethanol. Ethylene glycol and 1,4-butanediol are more preferred in that they can improve the heat resistance and oil resistance of the polyester resin (B), and 1,4-butanediol is most preferred. Also, as a part of the glycol component, a polyol having three or more functional groups such as glycerin, trimethylolpropane, pentaerythritol, etc. may be used, and from the viewpoint of preventing gelation of the encapsulating resin composition, the content of the glycol component is preferably 10 mol % or less, more preferably 5 mol % or less, of the total glycol components of the polyester resin (B). The polyester segment is preferably composed of a polyester segment mainly composed of terephthalic acid and 1,4-butanediol.
[0051] As the component constituting the polyester segment, those comprising butylene terephthalate units or butylene naphthalate units are preferred because the polyester resin (B) has a high melting point and can improve heat resistance, and also from the standpoints of moldability and cost performance, and those comprising butylene terephthalate units are particularly preferred.
[0052] <Sealing resin composition> The encapsulating resin composition of the present invention contains the polyester resin (A) and the polyester resin (B), and the ratio M(A):M(B) of the mass M(A) of the polyester resin (A) to the mass M(B) of the polyester resin (B) is in the range of 90:10 to 70:30. Since the melt viscosity, adhesive strength, and oil resistance are good, M(A):M(B) is preferably 88:12 to 73:27, more preferably 85:15 to 75:25, and particularly preferably 83:17 to 78:22. Here, encapsulation refers to wrapping precision parts and the like without gaps so that they do not come into contact with the outside air in order to prevent dust and water. The encapsulating resin composition of the present invention is excellent in long-term reliability, and is therefore suitable for encapsulating precision parts, particularly electric and electronic parts.
[0053] The total amount of the polyester resin (A) and the polyester resin (B) in the encapsulating resin composition is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. It is also preferably 99.9% by mass or less, more preferably 99.5% by mass or less, and even more preferably 99% by mass or less. By keeping it within the above range, the melt viscosity, adhesive strength, and oil resistance are improved. The encapsulating resin composition can further contain an antioxidant (C) to prevent oxidation of the polyester resin (A) and the polyester resin (B).
[0054] The encapsulating resin composition can be obtained by melt-kneading the polyester resin (A) and the polyester resin (B), and optionally the antioxidant (C), at a die temperature of 160°C to 220°C using a twin-screw extruder. The die temperature is preferably 170°C or higher, more preferably 180°C or higher. Also, it is preferably 210°C or lower, more preferably 200°C or lower. By keeping the temperature within the above range, it is possible to obtain an encapsulating resin composition having good melt viscosity, adhesion, and oil resistance.
[0055] <Antioxidants (C)> The antioxidant used in the present invention is not particularly limited as long as it can prevent the oxidation of the polyester resin (A) and the polyester resin (B), and hindered phenol-based antioxidants, phosphorus-based antioxidants, thioether-based antioxidants, etc. can be used. For example, hindered phenol-based antioxidants include 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, 1,1,3-tri(4-hydroxy-2-methyl-5-t-butylphenyl)butane, 1,1-bis(3-t-butyl-6-methyl-4-hydroxyphenyl)butane, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-benzenepropanoic acid, pentaerythrityl tetrakis(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 3-(1,1-dimethylethyl)-4-hydroxy-5-methyl-benzenepropanoic acid, and the like. Noic acid, 3,9-bis[1,1-dimethyl-2-[(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane, 1,3,5-trimethyl-2,4,6-tris(3',5'-di-t-butyl-4'-hydroxybenzyl)benzene, and phosphorus-based compounds such as 3,9-bis(p-nonylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane and 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]Undecane, tri(mononylphenyl)phosphite, triphenoxyphosphine, isodecyl phosphite, isodecylphenyl phosphite, diphenyl 2-ethylhexyl phosphite, dinonylphenyl bis(nonylphenyl) ester phosphorus acid, 1,1,3-tris(2-methyl-4-ditridecylphosphite-5-t-butylphenyl)butane, tris(2,4-di-t-butylphenyl)phosphite, pentaerythritol bis(2,4-di-t-butylphenyl phosphite), 2,2'-methylenebis(4,6-di-t-butylphenyl Examples of the thioethers include 4,4'-thiobis[2-t-butyl-5-methylphenol]bis[3-(dodecylthio)propionate], thiobis[2-(1,1-dimethylethyl)-5-methyl-4,1-phenylene]bis[3-(tetradecylthio)propionate], pentaerythritol tetrakis(3-n-dodecylthiopropionate), and bis(tridecyl)thiodipropionate, which can be used alone or in combination.
[0056] The content of the antioxidant (C) is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, and even more preferably 0.5 parts by mass or more, based on 100 parts by mass of the total of the polyester resin (A) and the polyester resin (B). By making the content equal to or more than the lower limit, the long-term durability at high temperatures is improved. Also, it is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 1 part by mass or less. By making the content equal to or less than the upper limit, the adhesiveness is improved.
[0057] The encapsulating resin composition of the present invention may contain other resins such as polyester, polyamide, polyolefin, polycarbonate, acrylic, ethylene vinyl acetate, and epoxy, which do not fall under any of the polyester resin (A), polyester resin (B), and antioxidant (C) of the present invention, curing agents such as isocyanate compounds, epoxy resins, and melamine, fillers such as talc and mica, pigments such as carbon black and titanium oxide, and flame retardants such as antimony trioxide and brominated polystyrene, within a range that does not impair the effects of the present invention. By adding these components, adhesion, flexibility, durability, and the like may be improved. In this case, the polyester resin (A) is preferably contained in an amount of 70% by mass or more, more preferably 75% by mass or more, and even more preferably 80% by mass or more, based on the entire resin composition of the present invention. By making the content of the polyester resin (A) equal to or more than the lower limit, the excellent adhesion to electric and electronic parts, adhesion durability, and flexibility that the polyester resin (A) itself has can be expressed.
[0058] Furthermore, when the encapsulating resin composition of the present invention is required to have weather resistance, it is preferable to add a light stabilizer. Examples of the light stabilizer include benzotriazole-based light stabilizers, benzophenone-based light stabilizers, hindered amine-based light stabilizers, nickel-based light stabilizers, and benzoate-based light stabilizers. Benzotriazole-based light stabilizers include 2-(3,5-di-tert-amyl-2'hydroxyphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(2'-hydroxy-5'-methylphenyl)-benzotriazole, 2,4-di-tert-butyl-6-(5-chlorobenzotriazol-2-yl)phenol, 2-[2-hydroxy-3,5-di(1,1-dimethylbenzyl)]-2H-benzotriazole, and the like. Examples of the benzophenone-based light stabilizer include 2-hydroxy-4-(octyloxy)benzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-benzophenone-5-sulfonic acid, 2-hydroxy-4-n-dodecyloxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-2'-dihydroxy-4-methoxybenzophenone, and 2,2'-dihydroxy-4,4'-dimethoxybenzophenone.Examples of hindered amine light stabilizers include bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, dimethyl succinate·1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine polycondensate, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl) imino}hexamethylene(2,2,6,6-tetramethyl-4-piperidyl)imino}], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-s-triazine-2,4,6(1H,3H,5H)trione, tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)-s-triazine-2,4,6-(1H,3H,5H)trione, etc. Nickel-based light stabilizers include [2,2'-thio-bis(4-tert-octylphenolate)]-2-ethylhexylamine-nickel-(II), nickel dibutyldithiocarbamate, [2',2'-thio-bis(4-tert-octylphenolate)]-n-butylamine-nickel, etc. Benzoate-based light stabilizers include 2,4-di-t-butylphenyl-3,5'-di-tert-butyl-4'-hydroxybenzoate. These light stabilizers can be used alone or in combination. When added, the amount is preferably 0.1% by mass or more and 5% by mass or less based on the entire encapsulating resin composition. By adding 0.1% by mass or more, weather resistance effects can be achieved. By adding 5% by mass or less, adhesion, flame retardancy, etc. can be improved.
[0059] The composition and composition ratio of the polyester resin (A) and the polyester resin (B) can be determined, for example, by dissolving the polyester resin (A) or the polyester resin (B) in a solvent such as deuterated chloroform and measuring the composition and composition ratio. 1 H-NMR and 13Examples of the method include C-NMR, and quantitative determination by gas chromatography after methanolysis of polyester resin (A) or polyester resin (B) (hereinafter, sometimes abbreviated as methanolysis-GC method). In the present invention, a method capable of dissolving polyester resin (A) and polyester resin (B) and 1 If there is a solvent suitable for H-NMR measurement, 1 The composition and composition ratio will be determined by H-NMR. 1 If the composition ratio cannot be determined by H-NMR alone, 13 C-NMR and methanolysis-GC methods will be adopted or used in combination.
[0060] The encapsulating resin composition of the present invention preferably has a melt viscosity of 5 to 2000 dPa·s at 220°C, which can be achieved by appropriately adjusting the types and blending ratios of the polyester resin (A) and the polyester (B) and, if necessary, the antioxidant (C). For example, increasing the copolymerization ratio of the polyalkylene glycol copolymerized in the polyester resin (A) or decreasing the molecular weight of the polyester resin (A) tends to lower the melt viscosity of the encapsulating resin composition of the present invention, while increasing the molecular weight of the polyester resin (A) tends to increase the melt viscosity of the encapsulating resin composition of the present invention. The melt viscosity at 220°C is a value measured as follows. That is, the encapsulating resin composition is dried to a moisture content of 0.1% or less, and then the encapsulating resin composition is heated to 220°C and stabilized, and is subjected to a pressure of 98 N / cm using a flow tester (model number CFT-500C) manufactured by Shimadzu Corporation. 2It is a measured value of the viscosity when the resin is passed through the mold at a pressure of 1000 dPa·s or more. When the melt viscosity is 2000 dPa·s or more, high resin cohesive strength and durability can be obtained, but when sealing a part with a complex shape, high-pressure injection molding is required, which may cause the destruction of the part. By using an encapsulating resin composition having a melt viscosity of preferably 1500 dPa·s or less, more preferably 1000 dPa·s or less, an encapsulated body (molded part) with excellent electrical insulation can be obtained at a relatively low injection pressure of 0.1 to 20 MPa, and the characteristics of the electric and electronic parts are not impaired. In addition, from the viewpoint of the injection operation of the encapsulating resin composition, a lower melt viscosity at 220°C is preferable, but considering the adhesiveness and cohesive strength of the encapsulating resin composition, the lower limit is preferably 5 dPa·s or more, more preferably 10 dPa·s or more, more preferably 30 dPa·s or more, and most preferably 50 dPa·s or more.
[0061] In the present invention, the adhesive strength between a specific member and an encapsulating resin composition is determined by preparing a test specimen in which the encapsulating resin composition is bonded between two plate-like members by molding, and measuring the shear adhesive strength of the test specimen. The method for preparing the test specimen and the method for measuring the shear adhesive strength are performed according to the methods described in the examples below.
[0062] The encapsulating resin composition of the present invention is molded by injecting it into a mold in which an electric / electronic component is set. More specifically, when a screw-type hot melt molding applicator is used, the composition is heated and melted at about 160 to 280°C, injected into the mold through an injection nozzle, and then after a certain cooling time, the molded product is removed from the mold to obtain the molded product.
[0063] The type of applicator for hot melt molding is not particularly limited, but examples include ST2 manufactured by Nordson Corporation and vertical extrusion molding machine IMC-18F9 manufactured by Imoto Manufacturing Co., Ltd. EXAMPLES
[0064] In order to explain the present invention in more detail, examples and comparative examples are given below, but the present invention is not limited to these examples. The measured values described in the examples and comparative examples were measured by the following methods.
[0065] <Melt point and glass transition temperature measurements> Using a differential scanning calorimeter "DSC220" manufactured by Seiko Denshi Kogyo Co., Ltd., 5 mg of the measurement sample was placed in an aluminum pan, the lid was pressed down to seal, and the pan was held at 250°C for 5 minutes. Next, the pan was quenched with liquid nitrogen, and then the pan was heated from -150°C to 250°C at a heating rate of 20°C / min. In the obtained curve, the intersection of the tangent (1) obtained from the baseline before the inflection point and the tangent (2) obtained from the baseline after the inflection point in the part where the inflection point appears in the DDSC as shown in Figure 1 was determined as the glass transition temperature, and the minimum point of the endothermic peak (marked with an x in the figure) was determined as the melting point.
[0066] <Acid value> A 0.1g sample of polyester resin (A) or polyester resin (B) was precisely weighed and dissolved in 10ml of benzyl alcohol by heating. The acid value was then determined by titration using a solution of 0.1N NaOH in methanol / benzyl alcohol (1 / 9 volume ratio). Phenolphthalein was used as the indicator.
[0067] <Specific gravity> Cut a bubble-free sample of polyester resin (A) or polyester resin (B) to 5 mm x 5 mm. Make five identical samples. Place the cut sample in a measuring cylinder containing calcium chloride solution at 30°C and stir well with a stirring rod to avoid foaming. Adjust the solution concentration so that the five samples float in the liquid for 2 to 3 minutes and then stop. Once the samples have stopped, float a hydrometer in the measuring cylinder and measure the hydrometer.
[0068] <Melting property (fluidity) test> Method for evaluating melt viscosity of polyester resin (A), polyester resin (B), and encapsulating resin composition Using a Shimadzu flow tester (CFT-500C), polyester resin (A), polyester resin (B), or encapsulating resin composition that had been dried to a moisture content of 0.1% or less was filled into the cylinder in the center of the heater set at 200°C. After 1 minute of filling, a load was applied to the sample via the plunger, and the molten sample was extruded from the die (hole diameter: 1.0 mm, thickness: 10 mm) at the bottom of the cylinder at a pressure of 1 MPa. The plunger's descent distance and descent time were recorded, and the melt viscosity was calculated. Evaluation criteria ◎: Melt viscosity @ 200℃ less than 500 dPa·s 〇: Melt viscosity @200℃ 500 dPa·s or more and less than 1000 dPa·s ×: Melt viscosity @200℃ 1000dPa·s or more
[0069] <Adhesion test (shear adhesion strength)> How to prepare shear adhesive strength test pieces The substrate was cut into sizes of 70 mm x 25 mm and 40 mm x 25 mm, and the surface was wiped with acetone to remove oil. Then, the substrates were overlapped by 10 mm in length so that the glass epoxy surface or PBT surface of the substrate would come into contact with the molten encapsulating resin composition, and the substrates were fixed inside a shear adhesion test mold so that the width was 25 mm and the thickness of the encapsulating resin composition to be molded was 1 mm. Then, using a screw-type hot melt molding applicator (Imoto Manufacturing Co., Ltd. vertical low-pressure extrusion molding machine IMC-18F9), the encapsulating resin composition with a moisture content of 0.1% or less was injected and molded. The molding conditions were as follows: molding resin temperature 250°C, molding pressure 3.5 MPa, dwell pressure 3.5 MPa, dwell time 20 seconds, and discharge rotation set to 80% (maximum discharge is 100%). The molded product was removed from the metal mold, and a shear adhesive strength test piece (substrate / encapsulating resin composition layer / substrate) was obtained in which the molded resin composition was sandwiched between the substrates.
[0070] Shear adhesive strength test method The shear adhesion test pieces were stored for one day under an atmosphere of 23°C and 50% relative humidity. Then, using an autograph (AG-IS manufactured by Shimadzu Corporation), each substrate was clamped with a chuck and the resin composition was peeled off in the shear direction to measure the shear adhesion strength. The pulling speed was 50 mm / min. Evaluation criteria ◎: Shear adhesive strength 2.5MPa or more ◯: Shear adhesive strength is 2.0 MPa or more and less than 2.5 MPa △: Shear adhesive strength is 1.0 MPa or more and less than 2.0 MPa ×: Shear adhesive strength less than 1.0 MPa The following two types of substrates (adherents) were evaluated. Non-resist glass epoxy (GE) board: Nikkan Industrial FR-4 PBT substrate: Polybutylene terephthalate (GF30%) Polyplastics: Duranex 3300
[0071] <Kerosene swelling characteristics (swelling rate after immersion in kerosene)> A flat plate of the encapsulating resin composition measuring 100 mm×100 mm×2 mm was produced by injection molding using a vertical injection molding machine (TH40E manufactured by Nissei Plastics Co., Ltd.). The injection molding conditions were: molding resin temperature 210°C, molding pressure 20MPa, cooling time 30 seconds, injection speed 10mm / sec. Three circular test pieces (diameter: 29.0±0.5mm, thickness: about 2mm) based on JIS K6262 (2013) were cut out from the molded flat plate using a cutter. The test pieces were then immersed in kerosene at room temperature (about 25°C) for 3.5 days, and the diameter and thickness of the test pieces were measured with calipers immediately after removal, and the product of the swelling ratios of the diameter and thickness was taken as the kerosene swelling ratio of the test pieces. Evaluation criteria: ◎: Kerosene swelling rate less than 5% by volume 〇: Kerosene swelling rate 5% or more and less than 10% by volume ×: Kerosene swelling rate 10% or more by volume
[0072] <Production Example of Polyester Resin (A)> In a reaction vessel equipped with a stirrer, a thermometer, and a distillation cooler, 1660 parts by mass of terephthalic acid, 1800 parts by mass of 1,4-butanediol, and 2.5 parts by mass of tetrabutyl titanate were added, and an esterification reaction was carried out at 170 to 220 ° C for 2 hours. After the esterification reaction was completed, 3000 parts by mass of polytetramethylene glycol "PTMG1000" (manufactured by Mitsubishi Chemical Corporation) having a number average molecular weight of 1000 and 5 parts by mass of hindered phenol-based antioxidant "Irganox 1330" (manufactured by Ciba-Geigy Corporation) were added, and the temperature was raised to 255 ° C., while the pressure in the system was slowly reduced to 665 Pa at 255 ° C. over 60 minutes. Then, a polycondensation reaction was carried out at 133 Pa or less for 30 minutes, to obtain a polyester resin (A-1). The melt viscosity, melting point, glass transition temperature, acid value, and specific gravity of this polyester resin (A-1) are shown in Table 1. Polyester resins (A-2) and (A-3) were synthesized in the same manner as polyester resin (A-1). The compositions and physical properties of each are shown in Table 1.
[0073] <Production Example of Polyester Resin (B)> In a reaction vessel equipped with a stirrer, a thermometer, and a distillation cooler, 125 parts by mass of terephthalic acid, 42 parts by mass of isophthalic acid, 225 parts by mass of 1,4-butanediol, and 0.068 parts by mass of tetrabutyl titanate were added, and the inside of the reaction tube was replaced with nitrogen, and then an esterification reaction was carried out at 170 to 220 ° C for 2 hours. After the esterification reaction was completed, the reaction system was heated from 220 ° C to 255 ° C, while the pressure in the system was slowly reduced to 5 Torr at 255 ° C over 60 minutes. Then, a polycondensation reaction was carried out for 30 minutes at 0.5 Torr or less to obtain a polyester resin (B-1). The melt viscosity, melting point, glass transition temperature, acid value, and specific gravity of this polyester resin (B-1) are shown in Table 1. In addition, a polyester resin (B-2) was synthesized by the same method as that of the polyester resin (B-1). The composition and physical properties of each are shown in Table 1. [Table 1]
[0074] The abbreviations in the table are as follows. TPA: terephthalic acid, IPA: isophthalic acid, AA: adipic acid, NDC: 2,6-naphthalenedicarboxylic acid, BD: 1,4-butanediol, PTMG1000: polytetramethylene glycol (number average molecular weight 1000), PTMG2000: polytetramethylene glycol (number average molecular weight 2000)
[0075] The polyester resin (A), the polyester resin (B), and the antioxidant (C) were melt-kneaded at a die temperature of 160°C to 220°C using a twin-screw extruder in the ratios shown in Tables 2 and 3 to obtain an encapsulating resin composition. The melt viscosity, adhesion, and kerosene swelling of the encapsulating resin composition were evaluated by the methods described separately. The evaluation results are shown in Tables 2 and 3 below.
[0076] [Table 2]
[0077] [Table 3]
[0078] The antioxidants (C) used in Tables 2 and 3 are as follows: Antioxidant (C-1): IRGANOX 1010 (registered trademark), manufactured by BASF Japan Ltd. Antioxidant (C-2): Lasmit LG (registered trademark), manufactured by Daiichi Kogyo Seiyaku Co., Ltd. [Industrial Applicability]
[0079] The encapsulating resin composition of the present invention has a low melt viscosity when encapsulating an electric / electronic substrate, has excellent adhesive strength to a glass epoxy substrate or a PBT substrate, and has excellent kerosene swelling, and is therefore useful as an encapsulating resin composition for electric / electronic components. The encapsulated electric / electronic component of the present invention is particularly useful in that it is excellent in adhesiveness and kerosene swelling, and thus suppresses leakage from electric / electronic components. The encapsulated electric / electronic component of the present invention is useful as a molded product such as various connectors, harnesses, electronic components, switches, and sensors having printed circuit boards for automobiles, communications, computers, and home appliances.
Claims
1. A resin composition for sealing electric and electronic components, comprising: a polyester resin (A) having a specific gravity of less than 1.20 and containing polyalkylene glycol as a copolymerization component; and a crystalline polyester resin (B) having a specific gravity of 1.20 or more and containing no polyalkylene glycol as a copolymerization component, wherein the mass ratio M(A):M(B) of the polyester resin (A) to the polyester resin (B) is 90:10 to 70:
30.
2. The resin composition for sealing electric and electronic components according to claim 1 , further comprising an antioxidant (C).
Citation Information
Patent Citations
Molding resin composition
JP2004210893A
Polyester resin for molding, resin composition and molded product using the same
JP2004277559A
Thermally conductive resin composition and molded article made of the same
JP2012117044A
